Rumex acetosa modulates platelet function and inhibits thrombus formation in rats - Dahye Jeong; Muhammad Irfan; Dong-Ha Lee; Seung-Bok Hong; Jae-Wook Oh; Man Hee Rhee (BMC, 2020)
Abstract Background The Rumex acetosa has been used in medicinal treatment, food technology and phytotherapeutics in Eastern Asia and many other countries. However, its effect on cardiovascular system and antiplatelet activity remained to be known. In this study, we examined the antiplatelet activity of R. acetosa in detailed manner to understand underlying mechanism. Methods To study this, whole blood was obtained from male Sprague Dawley (SD) rats and aggregation of washed platelets measured using light transmission aggregometry. Intracellular calcium ion concentration ([Ca2+] i ) was measured using Fura-2/AM while ATP release evaluated by luminometer. Activation of integrin αIIbβ3 analyzed by flow cytometry and clot retraction. Furthermore, we studied the signaling pathways mediated by R. acetosa extract by western blot analysis. Results R. acetosa extract markedly inhibited collagen-induced platelet aggregation and ATP release in a dose-dependent manner. It also suppressed [Ca2+] i mobilization, integrin αIIbβ3 activation and clot retraction. The extract significantly attenuated phosphorylation of the MAPK pathway (i.e., ERK1/2, JNK), MKK4, PI3K/Akt, and Src family kinase. Conclusion Taken together, this data suggests that R. acetosa extract exhibits anti-platelet activity via modulating MAPK, PI3K/Akt pathways, and integrin αIIbβ3-mediated inside-out and outside-in signaling, and it may protect against the development of platelet-related cardiovascular diseases.